Decursin inhibits the oxidation of low-density lipoprotein and protects human aortic endothelial cells against oxidative damage - Wang, Xueting; Yu, Jing; Ji, Binlong; Yang, Yuling (Cellular and Molecular Biology, 2020)
Atherosclerosis is the pathological basis of cardiovascular diseases (CVDs) which are the leading cause of death worldwide. The pathogenesis of atherosclerosis itself is complex. Low-density lipoprotein (LDL) oxidation has been shown to increase lipid peroxide levels in arterial wall of atherosclerosis lesion site. Decursin is a coumarin with a range of pharmacological effects. The present study investigated the inhibitory effect of decursin on LDL oxidation, and its protective effect against oxidative damage in human aortic endothelial cells (HAECs). Two models of oxidative damage were used in this study: Cu2+-induced LDL oxidative damage and 2,2’-azobis-2-methyl-propanimidyl, dihydrochloride (AAPH)-induced oxidative damage of HAECs. The inhibitory effect of decursin on LDL oxidation, and its protective effect on oxidative damage of HAECs were determined. The results showed that the level of thiobarbituric acid reactive substances (TBARS) was significantly increased by Cu2+, but was significantly and concentration-dependently reduced after treatment with decursin (p < 0.05). There were only a few viable cells in AAPH-treated group, but treatment with decursin led to significant, time- and concentration-dependent increases in their viability (p < 0.05). The AAPH-induced oxidative damage significantly increased the activity of lactate dehydrogenase (LDH) and level of reactive oxygen species (ROS), but significantly reduced the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx) (p < 0.05). However, treatment of HAECs with decursin significantly and concentration-dependently reduced the LDH activity and level of ROS, but significantly increased the activities of SOD and GPx, concentration-dependently (p < 0.05). It also significantly and concentration-dependently reduced apoptosis induced by AAPH (p < 0.05). These results show that decursin effectively inhibits LDL oxidation induced by Cu2+, and protects HAECs from oxidative damage caused by AAPH in vitro via a mechanism involving activation of SOD and GPx.